Development of IgY-Based Indirect Competitive ELISA for the Detection of Fluoroquinolone Residues in Chicken and Pork Samples - Sumed Yadoung; Ryoichi Ishimatsu; Zhen-Lin Xu; Korawan Sringarm; Supansa Pata; Marninphan Thongkham; Somporn Chantara; Mookda Pattarawarapan; Surat Hongsibsong (MDPI AG, 2022)
Fluoroquinolones (FQs) are among the antibiotics whose widespread use in farm-raised animals results in potentially harmful residues in the end products. Additionally, most Thai farmers use antibiotics. Amoxicillin and enrofloxacin were commonly used by pig farms, and hens were given enrofloxacin to prevent immunization side effects. Moreover, antibiotic overuse has harmed food safety in the long term, and the use of low-dose antibiotics causes bacterial resistance. Herein, an indirect competitive enzyme-linked immunosorbent assay (icELISA) was used to make a fast, easy, sensitive, and cost-effective method for monitoring FQs residues. After immunizing hens with mixed multi-hapten ciprofloxacin-bovine serum albumin (CPFX-BSA) with norfloxacin-bovine serum albumin (NFX-BSA), the IgY antibody purified from egg yolk was used for the detection of FQs residues in chicken and pork samples. The efficiency of the IgY antibody showed excellent sensitivity, with 50% inhibitory concentration (IC50) of enrofloxacin at 0.05 µg/mL, far below the MRLs defined by the EU for muscle samples, which was not to exceed 100 µg/kg. The recovery range for chicken muscle samples spiked with ENFX concentrations of 1.00-0.01 µg/mL was 86.65-112.71%, similar to pork samples, which were 84.24-117.22.2%. This method has a lot of potential for analyzing fluoroquinolones in complex samples quickly, easily, and at a low cost on-site. The IgY-based ic ELISA was developed to detect ciprofloxacin (CPFX), norfloxacin (NFX), and enrofloxacin (ENFX) residues; it confirms that IgY could be a promising choice for the detection of antibiotic residues in food samples.